ISOLASI DAN IDENTIFIKASI FUNGI ENDOFIT BATANG SESURU (Euphorbia antiquorum L.) SEBAGAI PENGHASIL ANTIBAKTERI DENGAN METODE KLT-BIOAUTOGRAFI - Asnita Asnita; Herwin Herwin; Rachmat Kosman; Ayyub Harly Nurung (Fakultas Farmasi UMI, 2020)
The research aimed to obtain antibacterial activity of isolate fermentate of endophytic fungi of antique spurge stem (Euphorbia antiquorum L.) on Staphylococcus aureus and Escherichia coli by TLC-Bioautography. The methods used in this research were isolation, purification and isolate screening. The screening results of endophytic fungi isolate of antique spurge stem showed the largest inhibitory zone in preventing both bacteria growth using code IFBS-03 and IFBS-06. The chromatogram profile of antibacterial activity isolate fermentate of the codes IFBS-03 and IFBS-06 showed active spots using TLC-Bioautographic method showed that code IFBS-03 isolate obtained Rf 0.87 and 0.27 values, indicating active spots on Staphylococcus aureus and Escherichia coli. The result of code IFBS-06 isolate obtained Rf 0.83 value active spots against Staphylococcus aureus and values Rf 0.83 and 0.27 value on Escherichia coli. Based on isolation and identification some chemical components obtained that dietyl ether ekstract of thin layer cromatography obtained chemicals components flavanoid at Rf 0.83 and 0.27 value with reagent Antimo (III) chloride.